Estudantes de música e o ensino coletivo de instrumentos musicais na UFCA - Santos, Tatiana da Silva (2021)
This dissertation presents and discusses the research’s results that aimed to understand the perceptions of students in the music course at UFCA about the collective practice of musical instruments and how they mobilized for musical learning in this context. Therefore, it was necessary to direct the study based on some guiding questions such as: What is the collective teaching of musical instruments in the students' conception? What did the students think about taking the discipline of instrumental practice in a group format? How did they identify with the material/repertoire worked in the classroom? How is the collective practice of musical instruments considered in the UFCA music course? Therefore, this study used as theoretical support some general perspectives on the teaching of musical instruments, in order to present aspects that have been discussed on the subject today. In order to illuminate the reflections undertaken in the research, we also used the study by Bernard Charlot on the theory of the relationship with knowledge, which allowed us to understand the meanings that students attribute to the collective practice of musical instruments and how they mobilize themselves in their processes. of learning. For the development of the research, a study with a qualitative approach was conducted, in which we used bibliographic research, documental research, and semi-structured interviews with students as data collection instruments. The main results showed that students considered the experience of playing in a group very positive and mentioned, mainly, contact with colleagues as a motivational factor for learning. In addition to the facilities that the group environment can provide, such as cooperation and interaction, students also highlighted some difficulties, such as the challenges that the teacher faces in this environment to deal with the expectations and particularities of students. Another important point concerns the repertoire worked in the disciplines of instrumental practice. On this issue, the students pointed out the importance of working with repertoires that are part of their experiences, providing opportunities for more significant contact with the musical content. Finally, about the mobilization in learning, some students said they had a good engagement in classes, in addition to studying at home. Others pointed out a certain lack of encouragement, mainly due to the repertoires worked on in the subjects. From this study, we hope to contribute by bringing reflections on the teaching of musical instruments in general and, specifically, on the collective teaching of musical instruments. We believe that highlighting the students' view of collective practice can contribute to promoting a contextualized teaching with the students' experiences and experiences.